Technological progress and finance: The effects of digitization on Brazilian banking fees - Mateus Feld; Tatiana Silva Fontoura de Barcellos Giacobbo; Wagner Eduardo Schuster (EconomiA, 2021)
Recent technological advancements and the digitization of most financial services have transformed the way by which individuals deal with their financial transactions. It has also affected the focus of financial institutions' investments, as well as the sectors' market dynamic, with the increasing number of start-ups and fintechs, which tends to lead to higher competition. Considering this scenario, our study explores the impacts that mobile and home banking had on bank fees charged to Brazilian consumers, from 2012 to 2019. As our theoretical framework, we use a network-city model, which is an evolution of the seminal linear and circular city models, while the econometric analysis is made using a time series model. Our findings show that bank fees were negatively affected by the digital banking platforms. In summary, the results indicate that the decrease on transport costs, caused by financial digitization and the widespread use of mobile and home banking, has reduced the price of bank fees to customers in the studied period.
Keywords: 330; Banks; Bank fees; Concentration; E-banking; Finance; Technology